1998
DOI: 10.1002/(sici)1521-4141(199803)28:03<844::aid-immu844>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 mRNA transcription is induced in mouse bone marrow-derived mast cells through an MHC class II-dependent signaling pathway

Abstract: We have previously shown that mouse bone marrow-derived mast cells (BMMC) can process and present immunogenic peptides to CD4 T cells. Here, we report on a T cell-dependent MHC class II-mediated mast cell activation resulting in IL-4 transcription and protein release. Presentation of optimal doses of ovalbumin peptide 323-339 resulted in IL-2 production by a specific T cell hybridoma and increase in IL-4 mRNA transcription in mast cells. IL-4 mRNA transcription increased by 200-fold in mast cells treated in IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Frandji et al have shown that BMMC, studied as APC, activated only a restricted spectrum of T cells compared with B cells [11]. However, the conditions for presentation of nominal antigen are fulfilled by BMMC which, in turn, were shown to undergo activation and to secrete IL-4 [11,12,32,47]. This raises the question of the influence of MC used as APC on the Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 99%
“…Frandji et al have shown that BMMC, studied as APC, activated only a restricted spectrum of T cells compared with B cells [11]. However, the conditions for presentation of nominal antigen are fulfilled by BMMC which, in turn, were shown to undergo activation and to secrete IL-4 [11,12,32,47]. This raises the question of the influence of MC used as APC on the Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, purified populations of mast cells can present Ags to T cells by either MHC class I-or class II-restricted mechanisms in vitro (8 -11), and contact with activated T cells in vitro can induce some mast cell populations to secrete histamine, TNF, and metalloproteinase 9 and to exhibit enhanced levels of IL-4 mRNA (12)(13)(14)(15). Besides representing a major potential source of TNF (16,17), which can have several effects that influence T cell recruitment, activation, and function (18 -21), at least some mast cells can produce many other factors, including CCL2, CCL3, CCL4, CCL5, XCL1, IL-16, and leukotriene B 4 , which also have the potential to enhance T cell recruitment to local inflammatory sites (5,(22)(23)(24)(25).…”
Section: Ast Cells Represent Important Effector Cells In Th2-andmentioning
confidence: 99%
“…Recently, thymic stromal lymphopoietin (TSLP), released by epithelial cells in response to physical injury and/or inflammatory cytokines, has been reported as a possible initiator of asthmatic responses through the potent stimulation of mast cells, to produce high levels of Th2 cytokines [51]. Mast cells are also known to present antigen, further providing a mechanism supporting Th2 differentiation and T cell activation [52][53][54][55]. In addition to the role of Th2-differentiated T cells, CD4…”
Section: Asthmamentioning
confidence: 99%